Analisis Risk Barriers and Mitigation Strategies for High-Rise Building Delays in Surabaya Using Fuzzy Logic - Ninda Qurmaulia Dhani; Michella Beatrix; Mochamad Firmansyah (Universitas Islam Raden Rahmat, Malang, 2026)
Delays in high-rise building projects negatively affect cost, quality, and schedule performance. This study aims to identify the main risk barriers and formulate appropriate mitigation strategies using a fuzzy logic approach. Data were collected from 80 valid respondents occupying strategic and operational roles in construction projects in Surabaya. Linguistic assessments (Low, Medium, High) were converted into Triangular Fuzzy Numbers and defuzzified using the centroid method to obtain crisp severity scores. The results indicate that cost overruns due to design revisions by the project owner (D4) represent the most critical risk barrier, with a defuzzification score of 3.717 (high category), followed by ineffective project control (E1) with a score of 3.483 (upper-medium category). The severity gap between D4 and the overall average of other indicators (≈3.30) shows a dominant external risk influence of approximately 0.40 points on the 1–5 fuzzy scale. Mitigation preferences reveal that risk avoidance is the dominant strategy for D4 (34 respondents), emphasizing design finalization before construction, while risk reduction is dominant for E1 (37 respondents), highlighting intensive monitoring and routine progress evaluation. Practically, prioritizing risks above the 3.50 threshold provides a structured basis for focusing managerial attention on the most critical delay drivers. Theoretically, this study demonstrates that fuzzy logic enhances decision accuracy by transforming subjective expert judgments into measurable and ranked risk severity values for high-rise construction projects.